RFC1 expansions are a common cause of idiopathic sensory neuropathy - Currò, Riccardo (Brain, 2021)
After extensive evaluation, one-third of patients affected by polyneuropathy remain undiagnosed and are labelled as having chronic idiopathic axonal polyneuropathy, which refers to a sensory or sensory-motor, axonal, slowly progressive neuropathy of unknown origin. Since a sensory neuropathy/neuronopathy is identified in all patients with genetically confirmed RFC1 cerebellar ataxia, neuropathy, vestibular areflexia syndrome, we speculated that RFC1 expansions could underlie a fraction of idiopathic sensory neuropathies also diagnosed as chronic idiopathic axonal polyneuropathy. We retrospectively identified 225 patients diagnosed with chronic idiopathic axonal polyneuropathy (125 sensory neuropathy, 100 sensory-motor neuropathy) from our general neuropathy clinics in Italy and the UK. All patients underwent full neurological evaluation and a blood sample was collected for RFC1 testing. Biallelic RFC1 expansions were identified in 43 patients (34%) with sensory neuropathy and in none with sensory-motor neuropathy. Forty-two per cent of RFC1-positive patients had isolated sensory neuropathy or sensory neuropathy with chronic cough, while vestibular and/or cerebellar involvement, often subclinical, were identified at examination in 58%. Although the sensory ganglia are the primary pathological target of the disease, the sensory impairment was typically worse distally and symmetric, while gait and limb ataxia were absent in two-thirds of the cases. Sensory amplitudes were either globally absent (26%) or reduced in a length-dependent (30%) or non-length dependent pattern (44%). A quarter of RFC1-positive patients had previously received an alternative diagnosis, including Sjögren’s syndrome, sensory chronic inflammatory demyelinating polyneuropathy and paraneoplastic neuropathy, while three cases had been treated with immune therapies.